ABOUT THE ARTICLE BY M.O. REVNOVA ET AL. «IMPROVING THE SYSTEM OF MASS HEALTH EXAMINATIONS OF CHILDREN» - Vladimir K. Tatochenko (Вопросы современной педиатрии)
Although the article is a muddled one, it is nothing but a cry from the heart of the pediatrician, who forcing herself fulfills (or tries to fulfill) the Order of the Ministry of Health of the Russian Federation No.1346 dated December 21, 2012. The author raises a number of questions and gives her answers to them. But before analyzing critical comments of the author and her offers, we should dwell on a number of statements on which her conclusions are based.